Genetic diversity in two leading Plasmodium vivax malaria vaccine candidates AMA1 and MSP119 at three sites in India. - Sonal Kale (Public Library of Science (PLoS), 2021)
Plasmodium vivax, a major contributor to the malaria burden in India, has the broadest geographic distribution and shows higher genetic diversity than P. falciparum. Here, we investigated the genetic diversity of two leading P. vivax vaccine candidate antigens, at three geographically diverse malaria-endemic regions in India. Pvama1 and Pvmsp119 partial coding sequences were generated from one hundred P. vivax isolates in India (Chennai n = 28, Nadiad n = 50 and Rourkela n = 22) and ~1100 published sequences from Asia, South America, North America, and Oceania regions included. These data were used to assess the genetic diversity and potential for vaccine candidacy of both antigens on a global scale. A total of 44 single nucleotide polymorphism (SNPs) were identified among 100 Indian Pvama1 sequences, including 10 synonymous and 34 nonsynonymous mutations. Nucleotide diversity was higher in Rourkela and Nadiad as compared to Chennai. Nucleotide diversity measures showed a strong balancing selection in Indian and global population for domain I of Pvama1, which suggests that it is a dominant target of the protective immune response. In contrast, the Pvmsp119 region showed highly conserved sequences in India and across the Oceania, South America, North America and Asia, demonstrating low genetic diversity in the global population when compared to Pvama1. Results suggest the possibility of including Pvmsp119 in a multivalent vaccine formulation against P. vivax infections. However, the high genetic diversity seen in Pvama1 would be more challenging for vaccine development.